Optimization of PCR protocols for primers PCAN-6-17 & PCAN 10-36 of green mussel perna viridis from Mabatang, Bataan using microsatellite markers - Penetrante, Alexis Ray L.
Green mussel is widely distributed along the coastal areas of the Philippines. Mussel farming started as early as 1950s however little information have been established regarding the use of published primers for green mussel for characterization. The use of molecular markers could potentially improve the maintenance of vigor of natural stock populations. In this study, primers PCAN-6-17 and PCAN-10-36 were optimized and showed distinct bands within the 30°C to 40°C temperature gradient. The final PCR conditions for both primers revealed an annealing temperature of 39°C and 36°C, respectively. PCAN-6-17 showed a band with an estimated length of 700bp while PCAN-10-36 showed three bands with an estimated length of 250bp, 450bp, and 500bp, respectively. Occurrence of low annealing temperature suggests inconsistencies such that primers may not properly bind to the targeted sequence thus partial annealing might happen. Because of low annealing temperature, it is best that primers PCAN-6-17 and PCAN-10-36 should be avoided in characterizing green mussel.